Mpox (Monkeypox): In-Depth Insight at the Current State of the Global Health Crisis - Etiology, Epidemiology, Detection, Treatment and Prevention Strategies - M Waheed Roomi (Disease and Health Research: New Insights Vol. 9, 2024)
Mpox, formerly known as the Monkeypox Virus, is once again in the headlines announcing its comeback. While still recovering from the 2022 outbreak - the World Health Organization (WHO), for the second time in as many years has declared mpox to be a global health emergency. The same uphill battle is being faced at the outset of this recurring threat. Mpox is a known quantity to the scientific community and has been for more than 60 years. First identified in humans during the 1970s, mpox is a viral zoonotic infectious disease transmitted from animals to humans and humans to humans. It is caused by the mpox virus - an enveloped double-stranded DNA virus belonging to the orthopoxvirus family. It is largely relegated to the tropical rainforests of Central and West Africa. It has been mostly ignored in Europe and the Americas until just recently when it has generated worldwide attention. Cases of the mpox infection first appeared sporadically amongst gay and bisexual men with Europe first reporting cases in mid-2022. Shortly thereafter, occurrences were seen in the metropolitan areas of New York, Chicago, San Francisco and Los Angeles. The 2022 outbreak was a turning point with over 100 countries reporting cases which had not previously been seen before. Mpox infections are transmitted through close personal contact with infected individuals, infected animals or mpox-tainted materials. The WHO has declared mpox a “Public Health Emergency of International Concern”. There are two distinct s of the mpox virus - Clade I and Clade II. Clade I’s origins have historically been linked to the Congo Basin, while Clade II’s origins have historically been linked to Western Africa. In 2022 the global outbreak was caused by Clade IIb and most recently, by Clade Ib in 2024. Mpox is genetically similar to smallpox. Although no treatment for the mpox virus exists, supportive care, antivirals and vaccines developed for smallpox have proven effective. Individuals infected with mpox demonstrate skin rashes and mucosal lesions accompanied by fever, chills, headaches, muscle aches, back pain, low energy, sore throat, and cough. These symptoms are similar to those infected with smallpox, but much more attenuated in nature. After a 3-week incubation period, mpox goes away on its own in approximately 2-5 weeks. Diagnostic testing and disease confirmation are performed via RT-PCR testing of genetic material from the infected areas and through the presence of lymphadenopathy (i.e. enlarged lymph nodes). This distinct symptom is what differentiates those who are infected with mpox versus those who are infected with either smallpox or chickenpox.